CRL-CUSUM chart in quality control - Toh, William. (2011)
The CRL-CUSUM chart is the most efficient control chart for attribute quality control. This chart integrates the advanced features of the run length chart and the CUSUM chart. It is able to significantly improve the effectiveness of the attribute quality control.